The Effects of Green Organizational Citizenship Behavior and Circular Economy Adoption on the Success of Green Accounting Initiatives through Cultural Readiness among Employees of Public Accounting Firms in West Java - Wijaya, Muhamad Rizky; Suwandi, Suwandi; Hapsari, Nesti; Pratiwi Octasylva, Annuridya Rosyidta; Sudarmanto, Eko (Westscience Press, 2025)
This study investigates the influence of Green Organizational Citizenship Behavior (GOCB) and Circular Economy (CE) implementation on the success of Green Accounting (GA) initiatives, mediated by Cultural Readiness (CR) among employees of public accounting firms in West Java. Using a quantitative approach, data were collected from 135 respondents via a Likert scale (1–5) and analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) version 3. The results reveal that both GOCB and CE implementation positively and significantly influence CR, which in turn significantly enhances GA success. Moreover, CR partially mediates the relationships between GOCB, CE implementation, and GA success, highlighting the critical role of organizational culture in supporting sustainability initiatives. These findings suggest that fostering environmentally responsible behaviors, embedding circular economy principles, and cultivating cultural readiness are essential for achieving effective Green Accounting practices in public accounting firms.